Optimal operation of the evaporator and combustion air distribution system in a pulp mill to maximize biomass recycling and energy efficiency. (20th September 2022) - Park, Jiye; Kim, Yurim; Lim, Jonghun; Cho, Hyungtae; Kim, Junghwan
Abstract: In the pulping process, the recovery boiler produces "green" steam without the use of fossil fuels as it burns the biomass (black liquor). However, because the black liquor concentration generated during the woodchip cooking is not suitable for combustion, it is concentrated using an evaporator that uses a large amount of steam energy for evaporation. The concentrated black liquor is sprayed to burn in a recovery boiler furnace, and combustion air is simultaneously supplied through an air distribution system. Biomass concentration and combustion air distribution should be optimized to realize sustainable cleaner production by maximizing biomass recycling and energy efficiency. In this study, the optimal operating conditions of the evaporator and combustion air distribution system in a pulp mill were determined simultaneously for biomass recycling and energy efficiency maximization. First, a process model was developed by integrating an evaporator and a recovery boiler furnace with an air distribution system. Using this model, the energy consumption of the evaporator, energy generation in the recovery boiler, and amount of recycled pulping chemicals were predicted for profit and cost estimation. Second, a mathematical model was developed to derive the optimal operating conditions. In this model, the net profit was calculated by subtracting the steam cost in the evaporation process from the profit of steam production and recovered pulping chemicals. Finally, the optimal biomass concentration and combustion air distribution were determined to maximize the net profit. As a result, the derived optimal operating conditions increased the annual power generation by 7, 491 MWh/y and the amount of recovered pulping chemicals by 68, 602 t/y. In addition, the net profit increased by 11.82%, and the annual CO2 emissions decreased from 2, 504 to 1, 361 tons, making the pulping process more sustainable. The findings of this study promote cleaner production in the pulping process by substituting fossil fuels with biomass and maximizing energy efficiency. Highlights: Biomass concentration and combustion air distribution in pulp mill were optimized. The evaporator and the recovery boiler furnace were integrated into a process model. Novel mathematical model optimizes the operating conditions. Biomass recycling and energy efficiency were maximized. Economic and environmental benefits of the pulping process were achieved.